New species, new records and re-description of spider mites (Acari: Tetranychidae) from India - Zeity, Mahran; Srinivasa, N.; Gowda, C. Chinnamade (Zootaxa, 2016)
Two species of Tetranychidae (Acari), Oligonychus neotylus sp. nov. from Zea mays and Pennisetum purpureum (Poaceae) and Tetranychus hirsutus sp. nov. from Gymnema sylvestre R. Br. (Apocynaceae) are described from Karnataka state, south India. Tetranychus bambusae Wang and Ma is recorded for the first time from India and re-described. Four other species are reported for the first time from India viz., Oligonychus coniferarum (McGregor), Oligonychus duncombei Meyer, Tetranychus marianae McGregor and Tetranychus okinawanus Ehara from Cupressus sp., an undetermined grass, Centrosema pubescens and Adenium obesum, respectively.